The pedagogical limitations of inclusive education - Pozo-Armentia, Araceli del; Reyero, David; Gil Cantero, Fernando (Educational Philosophy and Theory, 2020)
The aim of this article is to contribute to a better conceptual and pr actical delimitation of inclusive education. A pedagogy that reacts to the need to face the dilemmas of difference. An interpretive and crit ical methodology with a documentary basis and a normative-pedagogical perspective is used. The results show a tension between theoretical ap proaches and the practical achievements of inclusive education. The ar ticle concludes by considering the position that if the most basic def inition of education is essentially inherently inclusive, as it aims t o foster the maximum development of everyone, then for the same reason it must also essentially be differentiating. This is precisely becaus e the limits of inclusive education are in recognising and promoting e xcellence in difference, while the limits of differentiated education lie in recognising and promoting inclusion.
Keywords: Inclusive education; education for all; educational discrimination; equal education